Campagno, M., Gallego, J., García Mac Gaw, C.G. (Comps.). (2016). Regímenes Políticos en el Mediterráneo Antiguo. Estudios del Mediterráneo Antiguo / PEFSCEA, N° 11. Buenos Aires: Miño y Dávila. ISBN: 978-84-16467- 15-0, 289 páginas - Alfaro, Juan Pablo (2017)
Fil: Alfaro, Juan Pablo. Pontificia Universidad Católica Argentina; Argentina